The automobile technological systems. An empirical analysis of four European coutries - Riccardo Leoncini; Sandro Montresor (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
The aim of this paper is to study the automobile industry of the most important European countries (France, Germany, Great Britain and Italy) from a sectoral, system perspective. The main relationships within and between the building blocks constituting the automobile technological system are mapped and evaluated, both in cross-sectional and in temporal terms. The importance of the sectoral TS as the unit of our analysis appears evident at both levels. Some general sectoral properties emerge, which however hold in the four countries to a di erent extent, thus suggesting how the institutional set-up works as a di erentiating element. A sustained process of change in the various elements of the automobile TS is detected, nevertheless resulting in a relatively stable path of development. The countries considered reveal di erent patterns of motor vehicles trade specialisation in di erent geographical areas, with changes over time. Also foreign direct investments show the existence of very di erent trajectories and outward/inward balances.
Keywords: 330